Aggregate Formation of Oligonucleotides that Assist Molecular Imaging for Tracking of the Oxygen Status in Tumor Tissue. (28th June 2017) - Yoshihara, Kazuki; Takagi, Kohei; Son, Aoi; Kurihara, Ryohsuke; Tanabe, Kazuhito
Abstract: The use of DNA aggregates could be a promising strategy for the molecular imaging of biological functions. Herein, phosphorescent oligodeoxynucleotides were designed with the aim of visualizing oxygen fluctuation in tumor cells. DNA–ruthenium conjugates (DRCs) that consisted of oligodeoxynucleotides, a phosphorescent ruthenium complex, a pyrene unit for high oxygen responsiveness, and a nitroimidazole unit as a tumor‐targeting unit were prepared. In general, oligonucleotides have low cell permeability because of their own negative charges; however, the DRC formed aggregates in aqueous solution due to the hydrophobic pyrene and nitroimidazole groups, and smoothly penetrated the cellular membrane to accumulate in tumor cells in a hypoxia‐selective manner. The oxygen‐dependent phosphorescence of DRC in cells was also observed. In vivo experiments revealed that aggregates of DRC accumulated in hypoxic tumor tissue that was transplanted into the left leg of mice, and showed that oxygen fluctuations in tumor tissue could be monitored by tracking of the phosphorescence emission of DRC. Abstract : Live images : The use of DNA aggregates could be a promising strategy for molecular imaging of biological functions. Phosphorescent aggregates that consist of oligonucleotides and a ruthenium complex are reported with the aim of visualizing oxygen fluctuation in tumor cells.